SISTEM INFORMASI OBJEK WISATA JELITIK KABUPATEN BANGKA BERBASIS WEBSERVER - Fardhan Arkan (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2018)
Bangka has a beautiful tourist destination and attract tourists to visit, especially coastal tourism. One of them is a tourist destination in the village of Jelitik with beautiful and interesting beach tourism potential and is in one lane so that tourists have many options when visiting. Jelitik has beach tourism from Rambak Beach, Pantai Tikus, Tanjung Pesona, Pesona Bay and Tikus Mas Beach which is well known and widely visited by local people around Bangka. Currently, Jelitik does not have information system to provide complete information about the existing tourist attraction so as to facilitate the tourists when visiting. With the information system of this tourist attraction will facilitate the outsiders who want to know about tourist destinations in Jelitik and can be accessed using the Internet and introduce the tourist attraction widely to increase tourist arrivals. The tourist information system will make tourism in Jelitik will be widely known and make tourists who visit will get complete information. The development of information system of this tourist object will be based on webserver for management. The system will also build maps and profiles of this tourist destination is expected to introduce tours in Jelitik widely to the public using the Internet